EFEKTIFITAS MEDIA AUDIO VISUAL BERBASIS KINE MASTER DALAM MENINGKATKAN PENGUASAAN KOSAKATA BAHASA ARAB SISWA KELAS X MAN 3 JOMBANG - Mochamad Fawaidur Rochman; Afif Kholishon Nashoih (LPPM Universitas KH. A. Wahab Hasbullah, 2019)
In teaching and learning activities, educators are expected to be able to use innovative and creative learning media, by using the right media the materials to be conveyed can achieve the desired educational goals. Learning media that can be used vary greatly, one of which is audio visual based on Kinemaster. This study aims to determine the effectiveness of the media on vocabulary mastery in MAN 3 Jombang students in class X IPS-2 in the academic year 2019-2020. This study uses a quasi experimental method. In this study there are two classes, namely class X-IPS 2 as an experimental class and class X-IPS 1 as a control class each class of 50 students. Data collection techniques using pretest and post-test. Based on the results of the post-test for the experimental class has an average of 80,9 and the control class has an average of 70,9. While the results of the SPSS 16.0 analysis, sig values were obtained. (2-tailed) of the experimental class and the control class post-test is 0,00 which means it is greater than 0,05. So it can be concluded that H0 is rejected then there is a significant difference between the experimental class post-test and the post-test control class. based on these data it can be concluded that the use of audio visual media based on Kinemaster is an effective media in increasing the mastery of Arabic vocabulary. Keywords: Audio Visual, vocabulary, Arabic